Between Moral Hazard and Legal Uncertainty Ethical, Legal and Societal Challenges of Human Genome Editing (Technikzukünfte, Wissenschaft und Gesellschaft / Futures of Technology, Science and Society,, 2018)
Genome Editing Techniques are seen to be at the frontier of current research in the field of emerging biotechnologies. The latest revolutionary development, the so-called CRISPR technology, represents a paradigmatic example of the ambiguity of such techniques and has resulted in an international interdisciplinary debate on whether or not it is necessary to ban the application of this technique by means of a moratorium on its use for human germline modifications, particularly in human embryos in the reproduction process. However, given that other germline engineering techniques like mitochondrial (mt) DNA transfer techniques are already permitted and applied, the question arises what lies at the root of the apparent social unease about the modification of the human germline by Genome Editing Techniques like CRISPR. Against this background, the book seeks to make a substantial contribution to the current debate about a responsible and participatory framework for research on emerging biotechnologies by analysing underlying perceptions, attitudes, arguments and the reasoning on Genome Editing Techniques. Contents Mapping the current legal framing Theoretical Challenges Orientation markers for a Governance Frame in dealing with Genome Editing Target Groups Scientist, Policy Makers, Lecturers and students in the fields of Ethics, Philosophy, Theology, Law, Social and Political Science. The Editors Matthias Braun is assistant Professor at the Chair of Systematic Theology II (Ethics), Friedrich-Alexander University Erlangen-Nuremberg. Hannah Schickl is research assistant in the Interdisciplinary Research Group "Gene Technology Report", Berlin-Brandenburg Academy of Sciences and Humanities. Peter Dabrock is Professor of Systematic Theology/Ethics at the Friedrich-Alexander University Erlangen-Nuremberg and Chair of the German Ethics Council.